Reason And Revelation In Establishing Islamic Law (Case Study: Receiving Zakat For Educational Costs) - Nurfaizah, Nurfaizah; Kurniati, Kurniati; Misbahuddin, Misbahuddin; Misbahuddin Amin (Cita konsultindo, 2023)
Abstract: The conflict that occurs between reason and revelation has had a huge impact on the history of the development of Islamic law. And this should be a valuable lesson for Muslims now and in the future. The method used is a literature study with a qualitative approach. The purpose of this research is to find out how reason and revelation go hand in hand in the formation of Islamic law. the results of the research prove that reason and revelation both mean the basis for giving birth to Islamic law. This study also analyzes that there is no contradiction between reason and revelation. Factually the position between reason and revelation can be equal, but theologically revelation is the source of ideas for reason so that revelation (as a subject) has a higher position. conversely, reason cannot be a source of revelation, because reason is a creation while revelation is the word of God. The conclusion of this research is that modern Islamic law must be able to maximize its scientific reasoning (reason) in order to find meanings that are still hidden in the texts of the Qur'an and Hadith in answering the problems of life in the world without neglecting the benefits of the hereafter. Keywords: Conflict; Reason; Revelation, Islamic Law.